2012
DOI: 10.1371/journal.pone.0050950
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Uncertainties in N2O Emission Due to N Fertilizer Application in Cultivated Areas

Abstract: Nitrous oxide (N2O) is a greenhouse gas with a global warming potential approximately 298 times greater than that of CO2. In 2006, the Intergovernmental Panel on Climate Change (IPCC) estimated N2O emission due to synthetic and organic nitrogen (N) fertilization at 1% of applied N. We investigated the uncertainty on this estimated value, by fitting 13 different models to a published dataset including 985 N2O measurements. These models were characterized by (i) the presence or absence of the explanatory variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 35 publications
6
73
1
1
Order By: Relevance
“…Philibert et al (30) show an improved CI for the range of nonlinear and linear models. When not accounting for parameter uncertainty, the lower boundary of Philibert et al (31) coincides with ours, whereas the upper boundary is more conservative than ours for N-input levels >150 kg·ha −1 . Parameter uncertainty widens the CI in the work by Philibert et al (31) and brings our estimate entirely within the boundary for N inputs up to 250 kg·ha −1 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Philibert et al (30) show an improved CI for the range of nonlinear and linear models. When not accounting for parameter uncertainty, the lower boundary of Philibert et al (31) coincides with ours, whereas the upper boundary is more conservative than ours for N-input levels >150 kg·ha −1 . Parameter uncertainty widens the CI in the work by Philibert et al (31) and brings our estimate entirely within the boundary for N inputs up to 250 kg·ha −1 .…”
Section: Discussionsupporting
confidence: 80%
“…We determined the mean quadratic model and used a resampling procedure to obtain the 95% CI for all of the site-years in our dataset, excluding sites with N-fixing crops and bare soil. We compared this CI with 95% CIs for IPCC tier 1 methodology and for the range of six models used by Philibert et al (31), including and not including parameter uncertainty. Selecting only studies with four or more N-input levels in our dataset, we performed a procedure described by Kim et al (25) to classify all site-years into categories of linear, faster than linear (exponential), and slower than linear (hyperbolic) N 2 O emission increases with N input.…”
Section: Methodsmentioning
confidence: 99%
“…This response was greater than the default 1 % IPCC emission factor, and comes close to 8.5 % (with the appropriate unit conversion). The relationship may not be linear (Philibert et al, 2012), and the general additive mixed model (GAMM) was fitted to allow for non-linearity in the fixed effects. However, the exact form of the response to NH 3 deposition was not well constrained by the data, especially at the lower values, and a simple linear fit was justified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 emissions from fuel use and fertilizer production were calculated according to Lesschen et al (2011). Emissions from on farm energy use were based on Opio et al (2013) and Macleod et al (2013), who derived emission factors in terms of emission and/or energy per unit of animal product. CO 2 emissions from pesticide use were based on country average pesticide use from FAOSTAT and a general emission factor of 10.97 kg CO 2 -eq/kg active ingredient from BioGrace (2011).…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in a lower uncertainty in N 2 O soil emissions for Europe. Philibert et al (2012) and Leip (2010) suggested that the ranges of the IPCC N 2 O emission factors might be overestimated with the Tier 1 approach. This implies that our uncertainty estimates for N 2 O emissions in Latin America and Africa could be overestimated.…”
Section: Uncertainty In Ghg Emissions Estimated By Miterra-globalmentioning
confidence: 99%